Macroeconomic uncertainty, cultural traits and entrepreneurship. Issue 51 (1st November 2020) - Fan, Zhaobin; Cheng, Yongli; Anwar, Sajid
ABSTRACT: The relationship between macroeconomic uncertainty and entrepreneurial activities has been the subject of intense debate among researchers. However, existing empirical studies report mixed findings. By examining the mediating role of cultural traits, we attempt to reconcile the conflicting results concerning the direction of the relationship between macroeconomic uncertainty and entrepreneurial activities. Specifically, we argue that the effect of macroeconomic uncertainty on entrepreneurial activities varies across the cultural trait of uncertainty avoidance. In countries where the prevailing culture is overwhelmingly characterized by low uncertainty avoidance, macroeconomic uncertainty is positively associated with entrepreneurial activities. By contrast, in countries where the prevailing culture is overwhelmingly characterized by high uncertainty avoidance, macroeconomic uncertainty is negatively related to entrepreneurial activities. Using data on 36 countries over the 2006–2016 period and employing the negative binomial regression technique, we find empirical support for our hypotheses. A series of robustness tests confirm the reliability of our empirical results.